CONSTRUCTION FEATURES OF PERFORMING EXTERNAL REINFORCEMENT FROM COMPOSITE MATERIALS - Akramov Khusnitdin Akhrarovich; Davlyatov Shohrukh Muratovich; Kimsanov Bahromjon Ikromjon ogli; Nazirov Ayubkhon Sultonjon ogli (Journals Park Publishing, 2022)
This article presents methods for applying modern methods to increase the bearing capacity of existing buildings using carbon fiber, which are relevant today.
Keywords: load-bearing structure, carbon tape, composite materials, reinforcement methods, technology.